2012
DOI: 10.1063/1.4748288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pt bottom electrode texture selection on the tetragonality and physical properties of Ba0.8Sr0.2TiO3 thin films produced by pulsed laser deposition

Abstract: Electric field induced instabilities of thin leaky bilayers: Pathways to unique morphologies and miniaturization J. Chem. Phys. 138, 024705 (2013) Electric field-tunable BaxSr1−xTiO3 films with high figures of merit grown by molecular beam epitaxy Appl. Phys. Lett. 101, 252906 (2012) The penetration limit of poly(4-vinyl phenol) thin films for etching via holes by inkjet printing Appl. Phys. Lett. 101, 253302 (2012) The penetration limit of poly(4-vinyl phenol) thin films for etching via holes by inkj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…The lattice parameters calculated from the least‐square method for the BST films are a = 3.984 Å and c = 4.005 Å, which gives a lattice distortion ( c/a ) equal to 1.005. This value is similar to the one found in literature for BST (80/20) thin films deposited on platinized substrates at higher temperatures . However, the peak positions of BST layer are slightly shifted to higher 2θ values comparing to that of the target (green lines in Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The lattice parameters calculated from the least‐square method for the BST films are a = 3.984 Å and c = 4.005 Å, which gives a lattice distortion ( c/a ) equal to 1.005. This value is similar to the one found in literature for BST (80/20) thin films deposited on platinized substrates at higher temperatures . However, the peak positions of BST layer are slightly shifted to higher 2θ values comparing to that of the target (green lines in Fig.…”
Section: Resultssupporting
confidence: 90%
“…As is seen in the inset of Fig. (d), the data in the voltage range between 1.2 and 2.0 V can be well fitted with the PF mechanism and give the appropriate values of ϵ = 3.84, which is in a good agreement with the reported values for BST materials . The charge carrier transport in this region is governed by the photogenerated carriers developed in the whole region of ferroelectric film.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The work functions of polycrystalline Pt and ITO are 5.6 eV and 4.5 eV, respectively3039. This leads to an electric potential asymmetry, with a rectification ratio of 1.3, in the I-V curves of the Pt/BTO/ITO structures, as one can see in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Sakaliuniene et al have also shown that film porosity is reduced and therefore that the resistivity decreases from 85 to 25 µΩ cm when the argon pressure is reduced from 5 to 0.6 Pa [3]. In addition, it has been shown that the deposition temperature of these electrodes has a strong influence on the crystalline quality of the Pt film and thus on the electrical properties of the MFM stack [4][5][6][7][8]. Indeed, the well-ordered structure of the Pt electrode promotes crystal growth of the oxide ferroelectric film.…”
Section: Introductionmentioning
confidence: 99%